Proving Irreducibles

Prove that the polynomial

(xa1)(xa2)...(xan)1(x-a_1)(x-a_2)...(x-a_n)-1,

where a1,a2,...,ana_1, a_2, ..., a_n are distinct integers, cannot be written as the product of two non-constant polynomials with integer coefficients, i.e., it is irreducible.

#Algebra

Note by Sharky Kesa
7 years, 2 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Let f(x)=(xa1)(xa2)(xa3)..........(xan)1f(x) = (x-a_1)(x-a_2)(x-a_3)..........(x-a_n) - 1 For sake of contradiction let us consider f(x)f(x) can be written as the product of two polynomials with integer co-efficients,ie,f(x)=p(x)q(x)f(x) = p(x)q(x). For all i = 1,...,n we have f(ai)=p(ai)q(ai)=1f(a_i) = p(a_i)q(a_i) = -1. Since p(x)p(x) and q(x)q(x) are polynomials with integers co-efficients. we must have p(ai)=1p(a_i) = 1 and q(ai)=1q(a_i) = -1 OR p(ai)=1p(a_i) = -1 and q(ai)=1q(a_i) = 1

In either case we have p(ai)+q(ai)=0p(a_i)+q(a_i) = 0. Hence The polynomial p(x)+q(x)p(x) + q(x) must have n distinct roots. But the degrees of both p(x)p(x) and q(x)q(x) are less than n and hence p(x)+q(x)p(x)+ q(x) cannot have n roots. Hence Contradiction.

Eddie The Head - 7 years, 2 months ago

An interesting note here: Dropping the "distinct integer" restriction on the problem invalidates the claim. One simple counterexample is (x+2)(x+2)1=(x+1)(x+3)(x+2)(x+2)-1=(x+1)(x+3).

Daniel Liu - 7 years, 2 months ago
×

Problem Loading...

Note Loading...

Set Loading...